ACUTE TOXICITY OF THREE PESTICIDES (BUTACHLOR, COPPER OXYCHLORIDE AND CHLORPYRIFOS) ON THE MARINE BENTHIC AMPHIPOD APOHYALE GRANDICORNIS (KROYER, 1845) (CRUSTACEA: HYALIDAE) - Sotelo-Vásquez, Diana Lina (2019)
Pesticides have been widely used since ancient times in agriculture for the protection of crops from plagues. However, most of these generate high environmental pollution. Despite of law regulation, they continue to arrive in different ways to the ocean. The present work evaluates the toxicity of three commercial pesticides in Peru: the herbicide Butachlor, the insecticide Chlorpyrifos and the fungicide Copper Oxychloride, on the marine amphipod Apohyale grandicornis (Krøyer, 1845). Ecotoxicological bioassays were carried out in each one with standardized protocols, in addition to Potassium Dichromate sensitivity test. Likewise, based on acute test, the environmental risk of the three pesticides at the aquatic level was evaluated by calculating the risk quotient (RQs). According to the LC50 of the pesticides the sequence in descended order of toxicity was: Butachlor> Chlorpyrifos> Copper Oxychloride. For the Potassium Dichromate sensitivity test, an LC50 value of 13.04 mg·L-1 was found. The herbicide Butachlor registered the highest toxicity of all the pesticides evaluated at the 96 h of exposure in A. grandicornis with LC50 of 0.019 mg·L-1, showing a toxicity 1.11 times higher than Chlorpyrifos and 28.42 more than Copper Oxychloride. Finally, both Butachlor and Chlorpyrifos present an environmental risk on A. grandicornis. While, Copper Oxychloride was an environmental risk when using the safety factor to calculate the risk quotient.